2017
DOI: 10.1007/s10767-017-9258-6
|View full text |Cite
|
Sign up to set email alerts
|

Nigeria’s Soft Power Sources: Between Potential and Illusion?

Abstract: A major requirement for regional power status is the location and deployment of soft power attributes which may range from culture, political ideology, diplomacy, to sporting achievements, foreign policy articulation, tourism, media exports and language. While contemporary analysis of Nigeria's regional and continental power profile is almost entirely focused on economic and military aspects, an objective account of the state's power portfolio would be incomplete without a careful estimation of its soft power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This study has revealed a couple of Nigeria's soft power resources from the cultural perspective, highlighting film or movie production (Nollywood) and music with iconic superstars as an area of comparative advantage over other regional rivals. The country has also shown a high level of regional mettle in arts -literature, fashion and language, cuisines and sports (Ogunnubi & Uzodike 2016, Ogunnubi & Isike 2017, Tella 2018.…”
Section: Cultural Dimensionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has revealed a couple of Nigeria's soft power resources from the cultural perspective, highlighting film or movie production (Nollywood) and music with iconic superstars as an area of comparative advantage over other regional rivals. The country has also shown a high level of regional mettle in arts -literature, fashion and language, cuisines and sports (Ogunnubi & Uzodike 2016, Ogunnubi & Isike 2017, Tella 2018.…”
Section: Cultural Dimensionmentioning
confidence: 99%
“…The fame of Nollywood and the music industry stems from resilient Nigerians and non-governmental agencies projecting and raking up substantial non-oil revenues and massive employment for the country. Therefore, the Nigerian government must start investing significantly in the entertainment industry to further stretch its hold on the sector in the region in particular, as the industry has begun featuring prominently in the country's GDP (Yavuzaslan & Cetin 2016, Ogunnubi & Isike 2017, Tella 2018.…”
Section: Cultural Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barring South Africa, compared with other African states, there has been relative growth in the literature on Nigeria's soft power. Tella (2017Tella ( , 2018b and Ogunnubi and Isike (2018) engage the currencies, constraints and contradictions of Nigeria's soft power. Some studies offer a comparative perspective.…”
Section: Introductionmentioning
confidence: 99%